ANALYSIS EFFECT OF RISK, SHARE HOLDERS STRUCTURE AND LEVERAGE TOWARD FINANCIAL DISTRESSED FIRM - Kusuma, Mahayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This analysis is aimed to examine the effect of risk, shareholder structure, and leverage towards financial distressed firms in the existing companies in Indonesia Stock Exchange in the period 2010-2012. This study used purposive sampling with the number of samples obtained as many as 56 companies. Data analysis techniques in this study is logistic regression. The test results of logistic regression prove that the risk variable, and leverage have a positive and significant effect on the dependent variable, that is financial distress. While the shareholder structure variables have no significant effect on the financial distress. Â Key Words: Financial Distress, Risk, Share Holders Structure, Leverage